3D printed fiber sockets for plug and play micro-optics. (18th November 2020) - Nair, Parvathi S; Trisno, Jonathan; Wang, Hongtao; Yang, Joel K W
Abstract: Integrating micro-optical components at the end facet of an optical fiber enables compact optics to shape the output beam (e.g. collimating, focusing, and coupling to free space elements or photonic integrated circuits). However, the scalability of this approach is a longstanding challenge as these components must be aligned onto individual fiber facets. In this paper, we propose a socket that enables easy slotting of fibers, self-alignment, and coupling onto micro-optical components. This integrated socket can be detached from the substrate upon fiber insertion to create a stand-alone optical system. Fabrication is done using nanoscale 3D printing via two-photon polymerization lithography onto glass substrates, which allows multiple sockets to be patterned in a single print. We investigated variations in socket design and evaluated the performance of optical elements for telecom wavelengths. We obtained an alignment accuracy of ∼3.5 µ m. These socket designs can be customized for high efficiency chip to fiber coupling and extended to other spectral ranges for free-form optics.